Acute Arterial Ischemic Stroke in a Treated Child with Hunter's Syndrome: A Case Report and Review of the Literature - Sharma, Kamal; Cummock, Joshua; Maertens, Paul (Journal of Pediatric Neurology, 2021)
Enzyme replacement therapy (ERT) has limited therapeutic effects on neurologic, skeletal, and cardiovascular pathophysiology. We report an acute right-sided flaccid hemiparesis in an 11-year-old boy with the severe neuronopathic phenotype of Hunter's syndrome who was receiving weekly idursulfase ERT. Due to his psychomotor regression and epilepsy, his presentation to the hospital was delayed. Computed tomography scan of brain showed no acute changes or hemorrhage. Stroke code was not called as patient was already outside of the time window for tissue plasminogen activator (tPA) therapy. Brain magnetic resonance imaging (MRI) showed diffuse cortical and deep atrophy consistent with his baseline neurological status and restricted diffusion in the territory of the left-middle cerebral artery (MCA) consistent with recent infarction. T1-weighted MRI revealed low signal intensity of the left insular cortex, as well as volume loss, consistent with previous undiagnosed stroke in the same vascular territory. In addition, MR angiogram (MRA) demonstrated left terminal M1 segment MCA occlusion. Echocardiogram showed aortic root dilation and moderate aortic valve insufficiency. Patient was also noted to have bacteremia related to port infection. ERT is limited by blood–brain barrier and the underlying glycosaminoglycans (GAGs) extracellular tissue accumulation which produces a proinflammatory state. GAG and bacterial lipopolysaccharide (LPS) are known to activate toll-like receptor 4 (TLR-4). GAGs released in the extracellular space of intracranial vessels induce inflammation by activating the TLR-4 pathway which is exacerbated by bacterial LPS contributing to focal arteritis. Our case suggests the importance of GAGs in the activation of the TLR-4 pathway as a cause of stroke in Hunter's syndrome.
Keywords: cerebrovascular accident; mucopolysaccharidosis type II; enzyme replacement therapy; idursulfase; toll-like receptor 4; glycosaminoglycans